PENDIDIKAN AGAMA ISLAM PADA ERA REVOLUSI INDUSTRI 4.0 - Agustaria (CV. Arsy Persada Quality, 2025)
Islamic religious education must be adapted to the challenges and opportunities that exist in the industrial revolution 4.0 era because advances in information and communication technology greatly influence daily life. The emphasis on Islamic religious education in the industrial revolution 4.0 era must include several important elements. First, the use of technology in religious teaching is very important. The millennial generation, which tends to be active in the digital world, can be used to convey religious messages through social media, mobile applications and online platforms. Second, Islamic religious education in the era of the industrial revolution 4.0 must actively involve human resources. To increase their understanding of religion, teachers must provide opportunities for their students to talk, share opinions, and ask questions. Third, Islamic religious education must emphasize that Islamic values ​​are relevant to the social and global context faced by the millennial generation. Religious messages must be connected to social, environmental, peace and human rights issues, so that the millennial generation can see the relationship between religion and their daily lives. Fourth, Islamic religious education must teach human resources to have the ability to think critically and apply religious teachings in a broader context. They must also be taught to understand religious texts contextually and rationally. In the era of industrial revolution 4.0, Islamic religious education must adapt to technological developments and social challenges faced by the millennial generation. Technology integration, active participation, the importance of Islamic values ​​and the development of critical thinking are important aspects for forming a meaningful and meaningful understanding of religion for the millennial generation.